PENDAMPINGAN PENGOLAHAN TORTILA PISANG TONGKA LANGIT KEPADA KELOMPOK TANI DI DUSUN KERANJANG DESA WAYAME KOTA AMBON - Syane Palijama; Gilian Tetelepta (Universitas Pattimura, 2026)
After harvest, tongka langit bananas (Musa troglodytarum) are typically consumed by the people of Maluku by grilling, boiling, and frying. Therefore, technological advancements are needed to transform them into new products that have economic value in the producing areas and are durable for storage. Utilizing bananas to create new products can provide added economic value and contribute to the nutritional needs of consumers. The objective of this activity is to increase the knowledge and skills of the wider community in utilizing bananas by processing them into various products, one of which is tortillas. The methods used include presentations, interviews, tortilla production, and testimonials about the banana tortillas produced. The results of the implementation of PkM show that the level of knowledge of participants with assessment indicators, namely equipment and processing processes before the PkM activity were 30% and 60% respectively, after the PkM activity increased to 90%. The level of skill of participants with assessment indicators, namely equipment and processing processes before the PkM activity were 61.25% and 80% respectively, after the PkM activity increased to 93.75% and 100%.